Plants of an Eucalyptus clone damaged by Scolytidae and Platypodidae (Coleoptera) - Zanuncio, José Cola; Sossai, Marcos Franklin [UNESP]; Flechtmann, Carlos Alberto Hector [UNESP]; Zanuncio, Teresinha Vinha; Guimarães, Edylene Marota; Espindula, Marcelo Curitiba (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 2005)
O objetivo deste trabalho foi avaliar o ataque de Scolytidae e Platypodidae em talhão de clone Eucalyptus grandis x Eucalyptus urophylla na região de Montes Claros, Estado de Minas Gerais, Brasil. Discos de madeira com galerias desses insetos foram retirados de 15 árvores de eucalipto entre 0,5 e 1,5 m de altura. Após a coleta deste material, as árvores atacadas foram queimadas. Os indivíduos da ordem Coleoptera obtidos desses discos foram identificados como Premnobius cavipennis, Premnobius ambitiosus e Dryocoetoides cristatus (Coleoptera: Scolytidae) e Euplatypus parallelus (Coleoptera: Platypodidae). O ataque de D. cristatus, espécie nativa do Brasil, ao eucalipto ainda não havia sido relatado, o que mostra sua adaptação a essa planta.

Species of Scolytidae and Platypodidae were evaluated in a plantation using a clone of Eucalyptus grandis x Eucalyptus urophylla in the State of Minas Gerais, Brazil. Wood disks with galleries were taken from 15 eucalyptus trees between 0.5 and 1.5 m height. After collection, all trees attacked were burned. Woodborers obtained from these disks were identified as Premnobius cavipennis, Premnobius ambitiosus, Dryocoetoides cristatus (Coleoptera: Scolytidae) and Euplatypus parallelus (Coleoptera: Platypodidae). This is the first report of D. cristatus, a Brazilian native species, damaging eucalyptus, which shows its adaptation to this plant.
Plantas de Eucalyptus atacadas por Scolytidae e Platypodidae (Coleoptera)
Keywords: Premnobius; Dryocoetoides; Euplatypus; Premnobius; Dryocoetoides; Euplatypus